Pengaruh Tingkat Kompetensi, Independensi Dan Integritas Auditor Terhadap Kualitas Audit - Ida Ayu Made Kartika Sari (UNHI Press, 2022)
The location of this research in the Public Accounting Firm in Bali. Pick-up method the time sample used is non-probability sampling method with the purposive sampling based on certain considerations. The population in this study are auditors who work at the office of Public Accountant (KAP) in Bali. The sample used in this study as many as 99 respondents. Data analysis techniques used in this study are Multiple Linear Regressions. Based on the result of the study it can be seen that (1) competence significant positive effect on audit quality. (2) independence significat positive effect on audit quality. Suggestions that can begiven by researchers is a Public Accounting Firm in Bali is expected to be rountinely provide training to auditors, always apply the regulations in carry out audits strictly and always supervisethe auditors in carrying out auditing and guiding auditors.